Analisis Motivasi Guru Terhadap Belajar Murid di TK Anugerah Bengkayang - Lisa Anggela; Priska Vasantan (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine teacher motivation which has a positive impact on student learning at Anugerah Bengkayang Kindergarten. This type of research is a descriptive qualitative research that orginates from the sources studied and then analyzed in order to obtain learning process so far, where motivation is one of the supports for student success in the teaching and learning process at Anugerah Bengkayang Kindergarten.